2015
DOI: 10.4141/cjps-2015-084
|View full text |Cite
|
Sign up to set email alerts
|

N2 fixation ability of different dry bean genotypes

Abstract: Farid, M. and Navabi, A. 2015. N 2 fixation ability of different dry bean genotypes. Can. J. Plant Sci. 95: 1243Á1257. Common bean (Phaseolous vulgaris L.) is generally known as a weak N 2 fixer compared with other legumes. The availability of genetic variation for N 2 fixation potential of common bean supports the idea that symbiotic nitrogen fixation (SNF) in common bean can be improved through breeding. To assess the potential N 2 fixation of selected common bean genotypes, 12 bean varieties including three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 50 publications
(39 reference statements)
3
37
2
Order By: Relevance
“…The number of nodules per plant ranged from 2 to 646, nodule dry weight ranged from 1 to 601 mg per plant, and one nodule dry weight ranged from 0.10 to 13.24 mg (Figure 1). Differences between common bean genotypes for nodulation traits are often observed in greenhouse experiments, such as those reported by Akter et al (2014) and Farid & Navabi (2015), who reported a similar magnitude of variation to that observed in the present work.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The number of nodules per plant ranged from 2 to 646, nodule dry weight ranged from 1 to 601 mg per plant, and one nodule dry weight ranged from 0.10 to 13.24 mg (Figure 1). Differences between common bean genotypes for nodulation traits are often observed in greenhouse experiments, such as those reported by Akter et al (2014) and Farid & Navabi (2015), who reported a similar magnitude of variation to that observed in the present work.…”
Section: Resultssupporting
confidence: 91%
“…Akter et al (2014) also found a higher nodulation ability in Mesoamerican than in Andean genotypes, whereas Farid & Navabi (2015) found a greater number of nodules and nodule weights in Andean genotypes; however, nodules were more active in Mesoamerican genotypes. By the magnitude of the mean squares of variation sources estimated in the analysis of variance, it was not possible to state one of these two gene pools as showing larger genotypic variability for nodulation traits.…”
Section: Resultsmentioning
confidence: 97%
“…Conversely, Rodiño et al (2011) found that genotypes with a big nodule phenotype showed a good plant response and more beneficial for plant growth and seed yield. In contrast to the current study, Farid and Navabi (2015) found the common bean genotypes × environment interaction for grain yield production.…”
Section: Discussioncontrasting
confidence: 49%
“…The efficacy of rhizobial strains in nodulating and fixing atmospheric N with common bean varies with both the host genotypes and the Bacterium strains (Aguilar et al 1998;Caballero-Mellado and Martinez-Romero 1999;Farid and Navabi 2015;Michiels et al 1998;Moawad et al 1998). The prevailing environmental conditions significantly shape the diversity and distribution of indigenous rhizobia nodulating common bean (Wang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Graham [13] found that applications as low as 15 kg N ha −1 may reduce rates of N 2 fixation of dry bean by as much as 40%. Compared with other legumes dry bean is not an efficient N 2 fixing species and there appears to be a cultivar specificity in the strain of Rhizobia for nodulation [14]. Low and variable dry bean nodulation and N 2 fixation have been attributed to many factors including, high temperature, drought, soil acidity [15], high soil residual N, a short growing season, seasonal weather variation [16] [17], and differences in growth habit between cultivars [10].…”
Section: Introductionmentioning
confidence: 99%